Human and demographic capital in peripheral and core municipalities and regions and its development (northwest Bohemia) - Veselý, Vlastimil; Kubeš, Jan (Hungarian Geographical Bulletin, 2025)
The paper compares the human and demographic capital of central, suburban, semi-peripheral and peripheral municipalities of the Karlovy Vary Region and also the regions of Czechia and neighbouring regions in Germany. Peripheral municipalities are considerably distant from meso- and micro-regional towns in terms of time spent on public transport. The demographic capital of municipalities is assessed according to indicators of population development, natural and migration balance, and age structure. In the evaluation of human capital, indicators of education, unemployment, foreclosures, entrepreneurship, and housing construction are used. The assumption of low human capital in peripheral municipalities compared to more geographically exposed municipalities was not confirmed. Suburban municipalities have the highest human and demographic capital. Although the studied region borders the developed regions of Germany, it has the least favourable values of human and demographic capital of all Czech regions and neighbouring German regions. This is a consequence of the complete population exchanges after World War II, the existence of the Iron Curtain on the region’s borders with the West during the socialist (communist) period, the peripheral location of the region within Czechia, the inappropriate development of industry under socialism, and the problems of this sector and weak cross-border cooperation in the post-socialist period. The paper also presents strategies and measures to support human capital in the types of municipalities of the region and throughout the region.